KUALITAS BUTIR SOAL UAS BAHASA INGGRIS UNTUK SISWA MTs DI SAMARINDA - Sumaningsih Sumaningsih (Center of Language and Cultural Studies, 2015)
This study is aimed at seeing the item quality of English test used for Leaving Exam at SMP Samarinda. Analysis is used to see item difficulty (p), discrimination (D), distracter effectiveness, validity, and reliability. The results of analysis show that of 45 items, 19 (42.2%) must be dropped due to the poor p and 17 (37.8%) receive the low D. Analysis of p and D reveal that of 45 items, only 5 (11.1%) items are applicable, 21 (46.7%) need revision, and 19 (42.2%) should be dropped. The distracters are also poor, as 25 (55.6%) items have very poor distracters. Validity testing under Product Moment formula achieved low value (0.346) and reliability testing under KR-21 shows fair value (0.650).